2019
DOI: 10.3389/fphar.2019.00550
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness and Safety of Total Glucosides of Paeony in Primary Sjögren's Syndrome: A Systematic Review and Meta-Analysis

Abstract: Objective: To assess the effectiveness and safety of the total glucosides of paeony (TGP) on the treatment of primary Sjögren's syndrome (pSS) by conducting a meta-analysis. Methods: Eight databases were searched from their inception to December 10, 2018 for randomized controlled trials (RCTs). The Revman 5.3 software was used for this meta-analysis. Results: Nine RCTs which included 770 participants were identified. Pooled resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 44 publications
3
28
0
Order By: Relevance
“…Therefore, combination therapy including TGs with other therapies may be more effective than single treatment interventions. The present meta-analysis demonstrated that TGs combined with TGP significantly reduced the levels of CRP and immunoglobulins (IgG, IgM, and IgA) to an extent greater than TGs alone, which may be related to the synergistic effect of TGP on reducing immunoglobulins (43) or regulating immune homeostasis by modulating the Th17/Treg ratio (28). Despite the promising therapeutic potential of TGs for patients with SS, the incidence of adverse events is worthy of discussion.…”
Section: Discussionmentioning
confidence: 84%
“…Therefore, combination therapy including TGs with other therapies may be more effective than single treatment interventions. The present meta-analysis demonstrated that TGs combined with TGP significantly reduced the levels of CRP and immunoglobulins (IgG, IgM, and IgA) to an extent greater than TGs alone, which may be related to the synergistic effect of TGP on reducing immunoglobulins (43) or regulating immune homeostasis by modulating the Th17/Treg ratio (28). Despite the promising therapeutic potential of TGs for patients with SS, the incidence of adverse events is worthy of discussion.…”
Section: Discussionmentioning
confidence: 84%
“…Our meta-analysis suggested that the IGU group showed lower ESR than the non-IGU group, which was also observed in Shao’s study of 24 weeks ( Shao et al, 2020 ). Previous research studies have shown that HCQ or TGP can reduce ESR ( Feng et al, 2019 ; Bodewes et al, 2020 ); thus, IGU might enhance the anti-inflammatory activity of HCQ or TGP through a synergistic effect or independent pathways. In patients treated with IGU along with HCQ and GC, the RF level significantly decreased compared to that in patients treated with HCQ and GC.…”
Section: Discussionmentioning
confidence: 98%
“…Total glucosides of paeony (TGP) is a common Chinese medicine, which has been recorded with analgesic, anti‐inflammatory, immunomodulatory effects, and few side effects. Decreasing the substantial damage of glands and improving the secretion of lacrimal glands (Schirmer's test), are the significant functions of TGP 26 . At the same time, studies have shown that TGP can enhance the negative co‐stimulation pathway programmed cell death protein 1 (PD‐1)/PD‐L1 expression by reducing the expression of soluble PD‐1, further regulating Th17/Treg balance and reducing the production of autoantibodies.…”
Section: Managementmentioning
confidence: 99%